Research Concerning the Standard Locations of Meridian Points on the Yang Meridians of the Foot - KINOSHITA, Haruto; ODO, Yoshihiro; HOSHINO, Kazumi Rosa (Zen Nihon Shinkyu Gakkai zasshi (Journal of the Japan Society of Acupuncture and Moxibustion), 1989)
For the Yang Meridians on the feet we adopted the point locations described in the classics using the classics chronologically and expressed the point locations on the surface of the body in anatomical terms. When this was not possible they were expressed proportionately in terms of their location between standard points. The standard local scale for the foot was calculated through actual measurement using 3 fcun as the standard distance from the lateral malleolus to the ground. The altered scale of 2.5 fcun from the lateral malleolus to the ground and the 6.5 fcun used for the location of points between S44 and S41 in the KOITSU and a clinical local scale were used. Thus according to the 2.5 fcun measurement from the lateral malleolus to the ground for B63, B61 was determined as 1/3 of the way from the ground and B62 as 1/3 of the way from the lateral malleolus. B64, B65, and B66 were determined anatomically on the lateral superior border of the 5th metatarsal and the 5th toe. G41, G42 and G43 were determined anatomically on the dorsal aspect of the foot between the 4th and 5th metatarsals. Stomach Meridian, S44 on the dorsal aspect of the foot between the bases of the 2nd and 3rd proximal phalanges was established as a standard point and using S41 researched previously as a standard point, S44 was located 1/4 of the way posterior and S43, 1/3 of the way anterior. B67, G44 and S45 were located behind the nails on the 4th, 5th and 2nd toes.